2007
DOI: 10.1016/j.virol.2007.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Calcium enhances mouse keratinocyte differentiation in vitro to differentially regulate expression of papillomavirus authentic and codon modified L1 genes

Abstract: Here, we first wished to establish for mouse primary keratinocytes (KCs) the Ca(2+) concentrations that were associated with KC differentiation in vitro. Using the range of Ca(2+) concentrations (0-6 mM) to differentiate primary KCs in culture to varying extents for 2 days, we then examined how KC differentiation impacted on expression of papillomavirus (PV) native (Nat) and codon modified (Mod) L1 genes. L1 mRNAs transcribed from either Nat or Mod L1 genes were present in similar amounts in KCs exposed to six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…K14 expression was obviously enhanced in β-adducin-siRNA transfected keratinocytes without Ca 2+ treatment, while Ca 2+ treatment prevented the up-regulation of the K14 induced by β-adducinsiRNA transfection in keratinocytes (Fig. 5), consistent with our previous results that Ca 2+ down-regulated the expression of K14 in mouse primary keratinocytes [18]. Similar to our previous study, the expression of tubulin in both control and β-adducin-siRNA transfected keratinocytes without Ca 2+ treatment was distinctly higher than that in those cells with Ca 2+ treatment (Fig.…”
Section: Ca 2+ Blocks β-Adducin Sirna-caused Downregulation Of Involusupporting
confidence: 92%
See 2 more Smart Citations
“…K14 expression was obviously enhanced in β-adducin-siRNA transfected keratinocytes without Ca 2+ treatment, while Ca 2+ treatment prevented the up-regulation of the K14 induced by β-adducinsiRNA transfection in keratinocytes (Fig. 5), consistent with our previous results that Ca 2+ down-regulated the expression of K14 in mouse primary keratinocytes [18]. Similar to our previous study, the expression of tubulin in both control and β-adducin-siRNA transfected keratinocytes without Ca 2+ treatment was distinctly higher than that in those cells with Ca 2+ treatment (Fig.…”
Section: Ca 2+ Blocks β-Adducin Sirna-caused Downregulation Of Involusupporting
confidence: 92%
“…Both K1 and K10 among the keratin family are specifically expressed in the spinous and granular layers of the epidermis, which are recognized as the markers of keratinocyte differentiation [26]. During differentiation, the keratinocytes undergo a shape change from small and round to large and flat by expressing several differentiation markers including involucrin and keratin 10 [3,18]. Thus, together with our previous results, the present data suggest that the expression of β-adducin regulated by Ca 2+ is necessary for keratinocyte differentiation, implying further that β-adducin may play an important role in cell differentiation leading to the development of the epidermis and skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that an intermediate level of calcium (0.1- 0.16 mM) substantially induced the expression of early differentiation markers, such as K1 and K10, during the first 24 h upon calcium switch, whereas K1 and K10 was only induced in a small fraction of cells when treated with higher calcium medium (1 mM) 19,20 . However, the higher calcium medium (≥1 mM) has been widely used in many other studies to rapidly and robustly induce KC stratification and the expression of late differentiation genes, such as INV and LOR 4,21,22,23 . Based on our experience, an intermediate level of calcium, such as 0.2 mM CaCl 2 , leads to a gradual and slower onset of terminal differentiation, whereas a higher calcium levels (≥1 mM) drastically speed up the onset of KC terminal differentiation, leading to a shorter time window to study the cellular changes during differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated in vitro and in vivo that gene codon composition plays a role in differentiation-dependent expression of L1 proteins in KCs [21]. Using the KC culture system, we also proved that calcium enhances both mouse and human KC differentiation to differentially regulate expression of PV authentic and codon modified L1 ORFs [22]. Furthermore, generalised substitution of isoencoding codons shortens the duration of PV L1 protein expression in transiently L1-transfected KCs due to cell differentiation [23].…”
Section: Introductionmentioning
confidence: 72%